THE RELATIONSHIP OF PARENTING AND FOOD-FEEDING PATTERNS WITH THE NUTRITIONAL STATUS OF TODDLERS IN THE WORKING AREA OF THE UPT PUSKESMAS CIKEUSAL IN 2023 - Lestari, Eni Fuji; Putri, Dian Priharja (HEARTY, 2024)
Background:The prevalence of stunting among toddlers in Serang Regency is ranked third highest in 2022 at 8.96%, while the Cikeusal Community Health Center has the highest prevalence, namely 7.8%. The high rate of malnutrition and malnutrition among children under five is an indicator of the low nutritional status of society. A number of direct and indirect factors influence various nutritional problems faced by toddlers, including food consumption and parenting and feeding patterns. Purpose: To ascertain the relationship between feeding patterns and parenting styles and the nutritional status of toddlers in the Cikeusal Community Health Center UPT working area in 2023. Research Methodology: Quantitative analysis with cross-sectional design; 109 mothers with toddlers were selected by accident sampling technique; feeding patterns and parenting styles were measured using a questionnaire; the data was analyzed using the chi-square test. The Results: There was a relationship between feeding patterns and parenting styles and the nutritional status of toddlers in the Cikeusal Community Health Center working area in 2022. Conclusions and recommendations: feeding and parenting practices have an impact on toddlers' nutritional status. Mothers should be able to teach their children healthy eating habits and minimize their risk of stunting.